The Authoritative Guide on Harbor Management and Practice of Cloud Native Artifacts Such as Container Images and Helm Charts - Zhang, Haining; Wang, Yan. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Harbor is a major CNCF open source project, with thousands of production users all over the world. This book provides a comprehensive explanation of the open source cloud native registry: Harbor. Written by experts who contributed to and now maintain Harbor, the content covers its architecture, principles, functions, deployment and configuration, scanning artifacts, remote replication, operation and maintenance, customized development, API usage and success stories. The book offers a valuable guide for Harbor users, developers and contributors, cloud native software development engineers, test engineers, operational and maintenance engineers, IT architects and IT technical managers. It will also benefit university students in computer-related disciplines.
1 Artifact Management in The Cloud Native Environment -- 2 Installation and Configuration -- 3 Access Control -- 4 Security Policy -- 5 Remote Replication of Content -- 6 Advanced Management -- 7 Lifecycle Management -- 8 Harbor APIs -- 9 Governance Model of Harbor Community. .
Keywords: Cloud Computing; Open source software; Software engineering-Management.; Operating systems (Computers).; Cloud Computing; Open Source; Software Management; Operating Systems